2021
DOI: 10.11152/mu-2617
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasonography in head and neck Non-Melanoma Skin Cancer approach: an update with a review of the literature

Abstract: Non-Melanoma Skin Cancer is one of the most common cancer types and the face is the most affected region. The diagnosis of the skin cancer relies on clinical inspection, palpation, dermoscopy followed by incisional or excisional biopsy. When skin cancers are removed from the face, many factors are involved, including aesthetics. In addition, surgical planning with preoperative acknowledgement of the tumour margins is often the key to avoid incomplete excision, the need for reintervention, or in the prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…In a study on stage II CM patients, local recurrence represented 15% of all relapsing cases 2 . Risk factors for tumor recurrence include, among others, inappropriate or incomplete tumor removal (positive margin, R1–R2), cases without a wide excision, high depth of tumor invasion, perineural invasion, or aggressive subtypes at pathology 3–7 . At the same time, all kinds of skin tumors, epitheliomas, CM, etc., may recur as satellite nodules located around the scar but not in direct contact with it.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on stage II CM patients, local recurrence represented 15% of all relapsing cases 2 . Risk factors for tumor recurrence include, among others, inappropriate or incomplete tumor removal (positive margin, R1–R2), cases without a wide excision, high depth of tumor invasion, perineural invasion, or aggressive subtypes at pathology 3–7 . At the same time, all kinds of skin tumors, epitheliomas, CM, etc., may recur as satellite nodules located around the scar but not in direct contact with it.…”
Section: Introductionmentioning
confidence: 99%
“…Complete surgical excision is the most important management step, small lesions don't require any form of reconstruction, however for larger lesions some forms of flaps are usually required, the most common type of flaps are advancement flaps followed by rotational flaps, patients with involvement of one of the surgical margins require re-excision until negative margins achieved, however a study was done for patients with involvement of the surgical margins who underwent re-excision, they found that around half of the patients who have positive margins and underwent reexcision have no malignant cell in the second sample. [9,19,20] There are some recommendation to reduce the rate of skin cancer occurrence such as clothing, the use of hats, skin examination for early diagnosis of premalignant conditions or lesions at an early stage, daily use of sunscreens with SPF of 30 or greater, the use of sunglasses with UV light absorbing lenses, avoiding tanning booths, closely monitoring pigmented skin moles for any change, hyper-keratotic lesions and non-healing ulcers especially in the immuno-compromised patients. [21][22][23] In…”
Section: Discussionmentioning
confidence: 99%
“…Recently some authors used high frequency ultrasounds which can give information about the size of the mass and the depth of invasion. [9] The best management consists of timely diagnosis, good surgical excision with normal surgical margins, and some patients will require regional lymph node dissection. Some patients may require radiotherapy, chemotherapy or some types of immune therapy.…”
mentioning
confidence: 99%
“…[1][2][3] The most common types of NMSC are basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) with a ratio of approximately 4 to 1 and they are easily curable when detected in early stages. 3,4 While surgery is still the gold standard for the management of NMSC, various alternative approaches such as radiotherapy, systemic therapy, cryotherapy, and photodynamic therapy are utilized. 1,2 Radiotherapy plays an integral role in the treatment of NMSC.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐melanoma skin cancer (NMSC) is the most frequently diagnosed malignancy in Caucasians and the global incidence of NMSC is continuously rising 1–3 . The most common types of NMSC are basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) with a ratio of approximately 4 to 1 and they are easily curable when detected in early stages 3,4 . While surgery is still the gold standard for the management of NMSC, various alternative approaches such as radiotherapy, systemic therapy, cryotherapy, and photodynamic therapy are utilized 1,2 …”
Section: Introductionmentioning
confidence: 99%